The Efficiency of Using Computerized Program on the Level of Technical and Cognitive Performance in Basketball amongst Female in the Faculty of Physical Education at An-najah National University - Bader R. Salman (Sultan Qaboos University, 2015)
This study aimed to identify the effect of using computerized program on the level of technical and cognitive performance in basketball amongst female in the faculty of physical education at An-najah National University. The sample of the study consisted of (40) students, from basketball course, were divided equally among experimental and control groups. The Computerized Program (CP) was on the experimental group for 8-weeks, three times a week, and 50 minut for each class, while the traditional program was under the control group for the same duration. T-test were used for analyzing, means, standard deviation. The results of the study revealed a positive effect of using computerized program on the level of technical and cognitive performance in basketball .Also, the results indicated significant differences between experimental and control groups in the level of basketball performance as well as in knowledge domain of the course in favor of experimental group. Based on the findings of the study the researcher recommended the use of educational technology in teaching practical courses for physical education students.